(2, 12)
Because that is where the graphs intersect.
Answer:
i dont know
Step-by-step explanation:
sorry big homie on school
Answer:
The cooking club sales covers the expenditure when 2 piece of cakes are sold.
Step-by-step explanation:
Given:
Selling price of each piece of cake = $10
Cost for booth at fair = $10
Ingredients for each piece of cake = $5
We need to find the number of pieces of cake sold when the sales cover the expenditures.
Solution:
Let the number of pieces be 'x'
So We can say that the point at which the sales cover the expenditures can be calculated as Selling price of each piece of cake multiplied by number of pieces will be equal to Cost for booth at fair plus Ingredients for each piece of cake multiplied number of piece of cakes.
framing in equation form we get;
![10x =10+5x](https://tex.z-dn.net/?f=10x%20%3D10%2B5x)
Now Subtracting both side by '5x' using Subtraction property we get;
![10-5x=10+5x-5x\\\\5x=10](https://tex.z-dn.net/?f=10-5x%3D10%2B5x-5x%5C%5C%5C%5C5x%3D10)
Now Dividing both side by 5 we get;
![\frac{5x}{5}=\frac{10}{5}\\\\x=2](https://tex.z-dn.net/?f=%5Cfrac%7B5x%7D%7B5%7D%3D%5Cfrac%7B10%7D%7B5%7D%5C%5C%5C%5Cx%3D2)
Hence The cooking club sales covers the expenditure when 2 piece of cakes are sold.
Part A
Answer: The common ratio is -2
-----------------------------------
Explanation:
To get the common ratio r, we divide any term by the previous one
One example:
r = common ratio
r = (second term)/(first term)
r = (-2)/(1)
r = -2
Another example:
r = common ratio
r = (third term)/(second term)
r = (4)/(-2)
r = -2
and we get the same common ratio every time
Side Note: each term is multiplied by -2 to get the next term
============================================================
Part B
Answer:
The rule for the sequence is
a(n) = (-2)^(n-1)
where n starts at n = 1
-----------------------------------
Explanation:
Recall that any geometric sequence has the nth term
a(n) = a*(r)^(n-1)
where the 'a' on the right side is the first term and r is the common ratio
The first term given to use is a = 1 and the common ratio found in part A above was r = -2
So,
a(n) = a*(r)^(n-1)
a(n) = 1*(-2)^(n-1)
a(n) = (-2)^(n-1)
============================================================
Part C
Answer: The next three terms are 16, -32, 64
-----------------------------------
Explanation:
We can simply multiply each previous term by -2 to get the next term. Do this three times to generate the next three terms
-8*(-2) = 16
16*(-2) = -32
-32*(-2) = 64
showing that the next three terms are 16, -32, and 64
An alternative is to use the formula found in part B
Plug in n = 5 to find the fifth term
a(n) = (-2)^(n-1)
a(5) = (-2)^(5-1)
a(5) = (-2)^(4)
a(5) = 16 .... which matches with what we got earlier
Then plug in n = 6
a(n) = (-2)^(n-1)
a(6) = (-2)^(6-1)
a(6) = (-2)^(5)
a(6) = -32 .... which matches with what we got earlier
Then plug in n = 7
a(n) = (-2)^(n-1)
a(7) = (-2)^(7-1)
a(7) = (-2)^(6)
a(7) = 64 .... which matches with what we got earlier
while the second method takes a bit more work, its handy for when you want to find terms beyond the given sequence (eg: the 28th term)